The management capacity of rural La Pampa businessman : analysis of influential variables (Veterinary Science, 2017)
Administration capability of rural manager is, at present, a very important aspect to exit or faliure of agricultural enterprises. Regarding to yield knowledge as an index of this, in the present work it is studied if managers of northeast of La Pampa provine e.know and use this ratio. Its involved variables are also analized. The planned hypothesis is that yield knowledge depends of education level, specific realized capability curses and farms extension. Data were collected by means of direct enterview to a sample of the sector managers. X2-test was realized to check association or independence between cualitative variables, as soon as their association level. Later, a multi-variant analysis was realized, adding all the variables to check possible causal relations. Obtained results show association between yie1d knowledge and educational variables. That means managers with capability curses and upper-studies have a higher knowledge ofyie1d ratio. On the other hand, there's no an important association respect to farm extension variable. It is concluded that, ifyield know1edge is really an index of exit and survival, this work shows the importance ofmanagers capability
Keywords: Agricultural enterprise administration; Yield knowledge; Educational level; Capability curses